Identification keys to murid rodents of Argentina - Teta, Pablo; Jayat, J. Pablo (THERYA, 2021)
Muroid rodents are the most species-rich superfamily of rodents occurring in Argentina. Increased fieldwork with these mammals depicts the need of adequate keys to identify species on the base of external characters. In this contribution we provide three keys (one for families and subfamilies, and another two for Sigmodontinae and Muridae, respectively) for all known species of Cricetidae and Muridae distributed in Argentina (42 genera and 110 species). In addition to the dichotomous keys, and as a way to facilitate the identification, we include for each species a brief description of its distribution and the main habitats where it occurs.